Anesthesia in abdominal laparoscopic surgery - Enciso Nano, Jorge (2013)
Current technological development allows minimum access surgeries previously requiring big incisions resulting in high patient’s morbidity and trauma. Along with the development of technology and instruments for this type of surgery, anesthesiology also faced new challenges. Patient’s monitoring, drug and anesthetic management changed because new physiological variations and surgery complications have produced changes in hemodynamic and respiratory parameters, due to CO2 peritoneal cavity insuflation, increased intra-abdominal pressure and changes of position during the procedure.